Desvios, sobre arte e vida na contemporaneidade - Silva, Rubiane Vanessa Maia da (2012)
This essay discusses the relationship between art and life in contemporary. More specifically, we seek to, in some aspects of contemporary art, the materials of expression that occur in meetings with the power of life otherness. Creation and invention of other manners of perception and relationship with the living, porosity to the surface, passing affections. Artistic practices, especially those which constitute the process, act as new devices able to shoot methods, other possible, intense space-time relationship. We try to give visibility to the meetings, and performances and urban intervention, which towards the trials, the wanderings, detours and the rather more put themselves into question as triggers of lines of spaces and resistance. Force, in constitution that scrambles codes, drives rhythms and experimentation, with leads to certain gaps and mixed bodies. Laboratory ethical, aesthetic and political sensitivity of heterogeneity and enlightmen. The main conclusion of the study concerns the intersection between questioning and interfere with the lifestyles that are constituting the subjectivities that are taking place in the midst of so many anxieties and anesthetized. And so, actions and create tensions between body and word to trial andcall for more living and vibrating bodies. And think of the poetic art as that distracts us from the same, and contaminates, by micro-forces, the invention of new words on the word. Other odors, rumors, images, colors, textures, gestures, dances, smell looks...